EKSISTENSI PENDIDIKAN AGAMA ISLAM DI TENGAH DINAMIKA PLURALISME MODERN - Resti Yulastri; Sitti Hawa; Dian Rofi Anisa; Nadia Ismawati; Naila Azkiyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Islamic Religious Education has an important role in shaping students’ character and moral values amid modern pluralistic society. Modern pluralism influences social life and requires attitudes of tolerance and mutual respect among individuals. This article discusses the concept of Islamic Religious Education in modern life, the influence of pluralism, the role of Islamic Religious Education in instilling tolerance values, and the challenges of maintaining its existence in the modern era. The method used is a literature study. The results show that Islamic Religious Education plays a role in developing moderate, tolerant, and noble character. Therefore, learning innovation and strengthening religious values are needed to keep Islamic Religious Education relevant to the development of the times.